1999
DOI: 10.1128/jb.181.3.991-997.1999
|View full text |Cite
|
Sign up to set email alerts
|

High-Molecular-Mass Multi- c -Heme Cytochromes from Methylococcus capsulatus Bath

Abstract: The polypeptide and structural gene for a high-molecular-massc-type cytochrome, cytochromec 553O, was isolated from the methanotrophMethylococcus capsulatus Bath. Cytochromec 553O is a homodimer with a subunit molecular mass of 124,350 Da and an isoelectric point of 6.0. The hemec concentration was estimated to be 8.2 ± 0.4 mol of heme c per subunit. The electron paramagnetic resonance spectrum showed the presence of multiple low spin, S = 1/2, hemes. A degenerate oligonucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 66 publications
1
10
0
Order By: Relevance
“…The multihaem c-type cytochromes MCA0421 and MCA0423 were abundant at the lower copper concentrations, but showed a fine-tuned regulation of expression between~0 and 1.6 mM copper. Interestingly, and in line with previous reports of purified MCA0423 (Bergmann et al, 1999), our reduced-minusoxidized spectrum showed near identical wavelengths of local maxima of reduced MAC0423. These spectral features may also be representative for other members of the cytochrome c 553o family of proteins.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The multihaem c-type cytochromes MCA0421 and MCA0423 were abundant at the lower copper concentrations, but showed a fine-tuned regulation of expression between~0 and 1.6 mM copper. Interestingly, and in line with previous reports of purified MCA0423 (Bergmann et al, 1999), our reduced-minusoxidized spectrum showed near identical wavelengths of local maxima of reduced MAC0423. These spectral features may also be representative for other members of the cytochrome c 553o family of proteins.…”
Section: Discussionsupporting
confidence: 93%
“…Strikingly, the second cysteine in this motif appears to be substituted by histidine in MCA0423, thus disrupting the covalent attachment of haem. In line with this assumption, it has previously been demonstrated that MCA0423 contains eight c-type haem groups (Bergmann et al, 1999), while the other members of the multihaem cytochrome c 553o family are predicted to contain nine. Furthermore, Pfam analyses identified a putative PKD domain N-terminally in MCA0423 and MCA0338 (Fig.…”
Section: The Cytochrome C 553o Family Proteinsmentioning
confidence: 74%
See 1 more Smart Citation
“…Recently it has been speculated that some of the compounds degraded cometabolically by methane monooxygenase may actually serve as either a carbon or energy source for methanotrophs [4]. To be of any value to the cells, formaldehyde must be made in the oxidation of organic compounds such that the carbon can be converted either into biomass or further oxidized to carbon dioxide to generate more reducing equivalents than that consumed by the methane monooxygenase.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the type and abundance of the particular c‐type cytochrome present were found to vary with the bioavailability of copper ions in the growth medium (Table ) (Karlsen et al ., ). In sMMO‐producing cells, two members of the cytochrome c 553o family were abundant on the M. capsulatus Bath cellular surface [MCA0421 and MCA0423 (denoted occ in Bergmann et al ., )]. Both MCA0421 and MCA0423 are multiheme proteins containing nine and eight c‐type hemes respectively.…”
Section: Surface Associated Multi‐heme C‐type Cytochromesmentioning
confidence: 99%